Liver function indicators and risk of hepatocellular carcinoma: a bidirectional mendelian randomization study - Qin, Shanshan; Wang, Jing; Yuan, Haiqing; He, Jingzhen; Luan, Shoujing; Deng, Yan (Frontiers in Genetics, 2024)
Background: Observational studies showed an association between liver dysfunction and hepatocellular carcinoma (HCC), but the causality relationship between them is unclear. We aimed to determine whether there is a bidirectional causal relationship between liver function indicators (alanine aminotransferase, ALT; aspartate aminotransferase, AST; alkaline phosphatase, ALP; γ-glutamyltransferase, GGT) and HCC.: Our two-sample Mendelian randomization (MR) study acquired SNPs associated with the liver function indicators (ALT, n= 134,182; AST, n= 134,154; GGT, n=118,309; ALP, n= 105,030) and with HCC (n= 197,611) from publicly available genome-wide association studies (GWAS) of the East Asian ancestry in Japan (BioBank Japan, BBJ). Univariable MR analyses were performed to identify whether the genetic evidence of exposure was significantly associated with outcome.Multivariable MR analysis was conducted to estimate the independent effects of exposures on outcome.Results: Univariable MR analysis indicated that the level of ALT, AST and GGT was the risk factor for HCC incidence. Meanwhile, multivariable MR analysis revealed that the AST was the independent risk factor of HCC. The hazard ratio (HR) of the probability of HCC was 3.045 (95% confidence interval (95%CI), 1.697-5.463, P=0.003) for AST. The results of reverse MR analyses showed that gene-predictive HCC incidence could increase the level of AST (HR = 1.031, 95%CI: 1.009-1.054, P= 2.52x10 -4 ) and ALT (HR = 1.040, 95%CI: 1.019-1.063, P= 0.005). Meanwhile, HCC may be negatively correlated with ALP levels (HR = 0.971, 95%CI: 0.947-0.995, P =0.018).This study provides evidence to support that genetically predicted higher level of AST were related to increased risk of HCC, no strong evidence of a causal effect of genetically predicted ALP, ALP and GGT on HCC. In addition, genetic predisposition to HCC could influence blood concentration of ALT, AST and ALP. It may create a vicious cycle.